Making sense of the hotel trainees' internal request modification in Jordanian host-guest interaction - Rababah, Mahmoud; Harun, Minah; Shapii, Aspalila (oapun.org, 2019)
This paper examines the language of requests among the hotel trainees in Jordan. It seeks to explore the ways in which the trainees formulate requests in English as a foreign language at the service counter. Specifically, it discusses the extent to which the Jordanian trainees' use of internal modifiers when managing interpersonal and cross cultural communication diverges from that of the native speakers who are also the hotel supervisors and to relate any such divergences to politeness and cultural factors. The data collected include conversations between the trainees and hotel guests. The findings demonstrate that trainees under use internal modifiers to mitigate the imposition of the requests and they favor the marker 'please' more than any other modifiers. The findings also reveal that the trainees deviate from the native speakers' performance in terms of volume and types of modifiers. Some of these deviations might refer to Arabic language influence, pragmalinguistic and sociopragmatic transfer or to insufficient linguistic and pragmatic competences.